Environmental impact assessment on frequency of pesticide use during vegetable production - Islam, MA; Hossain, MT; Khatun, M; Hossen, MS (Progressive Agriculture, 2015)
An investigation was carried out to study frequency of pesticide use during vegetable production and its impact on environment. A structured questionnaire and researchers observation were used for this study. The data were collected from six different villages of sixty farmers at Mymensingh sadar upazilla in Bangladesh during February to May, 2013. More than half of the respondents (51.7%) were illiterate and lack of knowledge on pesticide use. About 60% respondents had 16-20 years farming experience and showed comparative knowledge on pesticide use. About 56.7% respondents practiced monthly communication with extension worker (Block Supervisor). About 66.7% respondents spent 04-06 hours to media every day. Half of the respondents had low level knowledge on pesticide use, where only 3.3% respondent showed high level knowledge on pesticide use. About half of the respondents (51.7%) used pesticide 16-20 times during the season. About 21.7% respondent used pesticide 21-25 times during the season. For selective vegetable okra showed highest frequency, about 16.7% respondents used pesticide 26-30 times during the season, while one third respondents (33.3%) used pesticide 16-20 times. About 58.3% respondent used pesticide 16-20 times for brinjal, while 8.3% respondents used 21-25 times. About two- fifth respondents (41.7%) used pesticide 16-20 times and 21-25 times for bitter gourd, while 8.3% respondents used 05-10 times and 10-15 times. About 58.3% respondent used pesticide 16-20 times for snake gourd, while 16.3% respondents used 21-25 times. About 66.7% respondent used pesticide 16-20 times for cucumber, while 16.7% respondents used 21-25 times. It indicated farmers used pesticide to their field 1-2 times in a week during the season in some vegetable cultivation. Therefore it has a high chance of remaining pesticide residues in the vegetables and soil. Moreover, most of the respondents applied pesticides without any protection measure and faced health problem due to expose with pesticide. Routine research work with wide public awareness, government and NGO participation, and government regulation are needed for food safety and sound environment. Progressive Agriculture 26 (2): 97-102, 2015